2010
DOI: 10.3358/shokueishi.51.213
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Dithiocarbamates and Milneb Residues in Foods by Gas Chromatography-Mass Spectrometry

Abstract: A highly sensitive gas chromatographic-mass spectrometric (GC-MS) method was developed for dithiocarbamates (DTCs) and milneb in foods. DTCs and milneb were extracted from foods with cysteineῌEDTA solution as sodium salts, and methylated with methyl iodide. Methyl derivatives of DTCs and milneb were cleaned up on a neutral alumina mini column and determined by GC-MS. The mean recoveries of DTCs and milneb were in the range of 72ῌ120ῌ, except for methiram. The quantification limits were 0.01 mg/kg (as CS 2 ) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…As with many other pesticide classes, the most selective methods for the determination of DTFs are based on gas chromatography coupled with-mass spectrometry (GC-MS) [ 6 ] and on reverse phase liquid chromatography coupled with optical, electrochemical, or mass-spectrometry detectors [ 7 , 8 , 9 , 10 ].…”
Section: Advances In Dtfs Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…As with many other pesticide classes, the most selective methods for the determination of DTFs are based on gas chromatography coupled with-mass spectrometry (GC-MS) [ 6 ] and on reverse phase liquid chromatography coupled with optical, electrochemical, or mass-spectrometry detectors [ 7 , 8 , 9 , 10 ].…”
Section: Advances In Dtfs Detectionmentioning
confidence: 99%
“…Nakamura et al described a GC-MS method for the detection of 10 dithiocarbamates in foods [ 6 ]. The compounds were extracted as water-soluble sodium salts with cysteine and ethylenediaminetetraacetic acid (EDTA) and then were derivatized by methylation.…”
Section: Advances In Dtfs Detectionmentioning
confidence: 99%
“…Recoveries were 72–120%, except for methiram. The LOQ was 0.01 mg/kg (Nakamura et al , ). A GC‐ECD method was applied for the investigation of the matrix effect in apple, mango, papaya, banana, pineapple and melon extracts.…”
Section: Gas Chromatographymentioning
confidence: 99%
“…1A) and milneb (Fig. 1B), containing the 1,3,5-thiadiazine-2-thione moiety, were developed as the important agricultural nematicide and fungicide, respectively (Lam et al, 1993; Nakamura et al, 2010). Recently, Mao et al (2017) found that dazomet could be applied as a promising agricultural bactericide to effectively control ginger blast in field trials (Mao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%